2017
DOI: 10.1039/c7ra05922a
|View full text |Cite
|
Sign up to set email alerts
|

Production of acetic acid from ethanol over CuCr catalysts via dehydrogenation-(aldehyde–water shift) reaction

Abstract: A series of CuCr catalysts were prepared by co-precipitation method and used to produce acetic acid from ethanol via dehydrogenation-(aldehyde-water shift) reaction. The catalysts were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller analysis (BET), inductively coupled plasma atomic emission spectroscopy (ICP-AES), and temperature programmed reduction (TPR). The effects of copper contents and atmosphere on catalytic performance were investigated. The enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The scope of the AWS reaction on the optimized NCZA‐33 catalyst was subsequently extended to some homologues of aldehydes and alcohols and the results are summarized in Table 3. Consistent with the prior research, [3d] alcohols showed relatively high conversion but low carboxylic acid selectivity, for the intermediate product of aldehyde is more likely spreading to gas phase than performing in the AWS reaction. As a good hydrogenation element, Cu‐based catalyst is also active in dehydrogenation, so that the alcohols showed high conversion to the corresponding aldehyde.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The scope of the AWS reaction on the optimized NCZA‐33 catalyst was subsequently extended to some homologues of aldehydes and alcohols and the results are summarized in Table 3. Consistent with the prior research, [3d] alcohols showed relatively high conversion but low carboxylic acid selectivity, for the intermediate product of aldehyde is more likely spreading to gas phase than performing in the AWS reaction. As a good hydrogenation element, Cu‐based catalyst is also active in dehydrogenation, so that the alcohols showed high conversion to the corresponding aldehyde.…”
Section: Resultssupporting
confidence: 88%
“…1). When in the AWS reaction, one proton in water is to form molecular hydrogen while the hydroxyl group is incorporated into the carboxyl group [3d] . With using soft oxidants, reaction could be more gently thus selectivity of target product be enhanced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pt + Al2O3| Pd + C − −−−−−−−−−−−−−− → SM2 SCMAWilcox et al (2003) 11 CA Ethanol + H2O CuCr − −−−→ SM2 + 2 H2 SCMAXiang et al (2003) FTT: Fischer-Tropsch-type, NC: Non-catalytic, CA: Catalytic. PAH: polycyclic aromatic hydrocarbon.…”
mentioning
confidence: 99%